RELIABILITY EVALUATION OF MULTIPLE PERFORMANCE AEROENGINES BASED ON Gamma PROCESS AND MIXED DISTRIBUTION UNDER COMPETITIVE FAILURE (Jixie qiangdu)
In order to solve the reliability evaluation under the competitive failure of multiple performance aero-engines,multiple performance data was fused into an overall degradation data by the matrix similarity,and a nonlinear Gamma process with random effects was used to fit the overall degradation data to obtain the reliability function under multivariate degradation.Assume that multiple performance of the aero-engines have sudden failures,the optimal sudden failure distribution was selected by Anderson-Darling(AD)distribution test,the reliability function under sudden failures was obtained by the mixed distribution.Assume that degradation failure and sudden failure were independent,the reliability evaluation of the multiple performance aeroengines under competitive failure was realized.Finally,the effectiveness and accuracy of the model were verified by the case analysis.